The Values of Natural and Constructed Wetlands: A Meta-Analysis - Andrea Ghermandi; Jeroen C.J.M. van den Bergh; Luke M. Brander; Henri L.F. de Groot; Paulo A.L.D. Nunes (Tinbergen Institute, 2009)
The values of goods and services provided by natural and constructed wetlands are examined through a meta-analysis of 418 observations of the economic value of 186 wetlands. Water quality improvement, non-consumptive recreation, and provision of natural habitat and biodiversity turn out to be highly valued services. Substitution effects are observed through the negative correlation between values and proximity to other wetlands. Values are found to increase with anthropogenic pressure. Constructed wetlands are highly valued for biodiversity enhancement, water quality improvement, and flood control. This study provides a substantially new contribution in relation to previous meta-analyses of the wetland valuation literature.
Keywords: C81; Q24; 330; constructed ecosystems; economic valuation; constructed wetlands; meta-regression; wetland values; Feuchtgebiet; Willingness to pay; Meta-Analyse